2015
DOI: 10.1097/psy.0000000000000161
|View full text |Cite
|
Sign up to set email alerts
|

Mood and Anxiety Disorders in Chronic Fatigue Syndrome, Fibromyalgia, and Irritable Bowel Syndrome

Abstract: Mood and anxiety disorders are more prevalent in individuals with FSSs, and particularly CFS, than in individuals without FSSs. However, most individuals with FSSs do not have mood or anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 30 publications
5
51
0
4
Order By: Relevance
“…Again, the rates are above the expected levels for IBS and the population prevalence of these symptoms 13 . Thus, the entire disease entity (IBS, functional gastrointestinal disorders and other functional non-gastrointestinal disorders) has been included in the term `somatic symptom disorder' in the Diagnostic and Statistical Manual of Mental Disorders 5th Edition (DSM-5) 14 and in psychiatric or psychosomatic clinical management 15 .…”
Section: Epidemiologymentioning
confidence: 80%
“…Again, the rates are above the expected levels for IBS and the population prevalence of these symptoms 13 . Thus, the entire disease entity (IBS, functional gastrointestinal disorders and other functional non-gastrointestinal disorders) has been included in the term `somatic symptom disorder' in the Diagnostic and Statistical Manual of Mental Disorders 5th Edition (DSM-5) 14 and in psychiatric or psychosomatic clinical management 15 .…”
Section: Epidemiologymentioning
confidence: 80%
“…For example, a genetic risk score analysis demonstrated that migraine with comorbid depression was more genetically related to depression than to pure migraine, which suggests that migraine might develop as a consequence of different polygenic backgrounds [71]. Similarly, a large general population cohort study confirmed that FM, CFS and IBS increase the odds of depression and anxiety but that most patients who suffer from FM, CFS and IBS have no mood or anxiety disorder [72]. …”
Section: Discussionmentioning
confidence: 99%
“…CFS and FMS are known for substantial clinical and diagnostic overlap, for example, chronic pain and fatigue are common in both patient groups. The two syndromes are often comorbid; up to 80% of CFS patients reported a history of clinician-diagnosed FMS [4,5]. This has resulted in the hypothesis that these syndromes share etiological pathways [6].…”
Section: Introductionmentioning
confidence: 99%